Consistency in stroke synchronisatiom patterns of crew-boat (k2) sprint kayaking over a four-week period - Tay, C. S.; Kong, P. W. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to compare the stroke synchronisation patterns of a sprint kayak crew (two-seater K2) over a four-week precompetition period. This case study centred on two female paddlers from a national sprint kayak team. High-speed (120 Hz) sagittal-view videos were recorded of a 200-m timetrial each week, for four weeks. Video analysis identified the extent of stroke synchronisation within the crew at four key positions of the stroke cycle (catch, immersion, extraction and release). Results showed similar patterns of offset across the four sessions, whereby the back paddler was either in time or slower to reach the catch position (91% of all strokes analysed), but faster to reach the release position (81% of all strokes analysed). It is likely that an experienced sprint kayak crew may be identified by their stroke synchronisation pattern.